2018
DOI: 10.1155/2018/4901242
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Serotonin and Pain in Patients with Chronic Low Back Pain before and after Spinal Surgery

Abstract: Introduction In this study we are aiming to evaluate the changes of serum serotonin and its association with pain in patients suffering from chronic low back pain before and after lumbar discectomy surgery. Patients and Methods A prospective study was performed on the patients referring to the outpatient clinic in Besat hospital, Hamadan University of Medical Sciences, Hamadan, Iran, during 2016. A 2 mL fasting blood sample was collected from each patient at preoperative day 1 and postoperative day 14 and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In addition, it has been suggested that the peripheral serotonergic system is negatively implicated in AD ( Kumar et al, 1995 ). Moreover, a negative association has been found between peripheral 5-HT amount and pain perception after different noxious stimuli ( Ernberg et al, 2000 ; Farhanchi et al, 2018 ). On the other hand, melatonin (MEL), a circadian rhythm–regulated hormone, has been shown to be protective in neurodegeneration associated with AD ( Savaskan et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been suggested that the peripheral serotonergic system is negatively implicated in AD ( Kumar et al, 1995 ). Moreover, a negative association has been found between peripheral 5-HT amount and pain perception after different noxious stimuli ( Ernberg et al, 2000 ; Farhanchi et al, 2018 ). On the other hand, melatonin (MEL), a circadian rhythm–regulated hormone, has been shown to be protective in neurodegeneration associated with AD ( Savaskan et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…AB reduced the reaction time in both the first and second phases of the formalin test, similar to the effects of Tra, a typical central antinociceptive medicine, thus confirming AB's analgesic properties. Neurotransmitters such as serotonin are reported to influence the nociception threshold (Farhanchi et al, 2018). In this study, AB exhibited regulatory activities on the levels of nNOS, 5-HT and NE in the serum and brains.…”
Section: Discussionmentioning
confidence: 68%
“…25 Some studies have found that people with chronic LBP show lower serum serotonin levels when compared to healthy persons. 26 Other authors reported a moderate increase of serotonin levels after autohemotherapy with ozone in patients with fibromyalgia, a disorder linked to CS, such as chronic LBP: this was matched to an improvement in symptomatology too. 27 Thus, we think that persons with a deficit of serotonin hormone and with consequently higher levels of pain-related anxiety and higher levels of CS could probably be favored by the O 2 O 3 therapy, also trough the increase of O 2 O 3 -induced serotonin levels.…”
Section: Discussionmentioning
confidence: 93%